TRANSPORT LOGISTICS AND WORKFORCE QUALITY: EVALUATING ACCESSIBILITY AND HUMAN RESOURCE QUALITY IN SELECTED NIGERIAN ORGANIZATIONS - Olusegun Timothy ODESOLA; Chukwudalu Daniel NWIZU (Scientific Journal of Silesian University of Technology. Series Transport)
This paper investigated how transport services affect the quality of work in selected organizations in Lagos Nigeria. As one of the most populous cities in Nigeria, Lagos deals with unique transport issues that impact the productivity and wellbeing of its workforce, with the region’s dynamic urban landscape that creates challenges and opportunities in the transportation system. A survey design was employed to gather data from 402 employees of the selected organizations sampled from a population of 6150 using research advisor. A structured questionnaire was employed to bring together the data for the study via random sampling technique. Descriptive and inferential analyses which included frequencies, percentages, mean, standard deviation and regression analysis were used to analyse the data. The findings revealed that availability of transport logistics services (t = 5.837, β = 0.313, ρ ≤ 0.05) had positive and significant effects on access to quality workforce, and reach to quality suppliers (t = 6.438, β = 0.308, ρ ≤ 0.05) significantly affects Cost of Transport logistics. On the overall, transport services in the study areas had a positive and significant effect on the quality of work in Lagos state, Nigeria. This study concluded that the quality of work in Lagos, Nigeria is significantly predicted by transport services. Hence, there is a need to strengthen the transport services so as to improve access to quality workforce, and the cost of transport.